ACE2 activation by xanthenone prevents leptin-induced increases in blood pressure and proteinuria during pregnancy in Sprague-Dawley rats - Hisham Saleh, Ibrahim; Gabrielle Ruth Anisah, Froemming; Effat, Omar (Elsevier Inc., 2014)
This study investigates the effect of ACE2 activation on leptin-induced changes in systolic blood pressure (SBP), proteinuria, endothelial activation and ACE2 expression during pregnancy in Sprague-Dawley rats. Pregnant rats were given subcutaneous injection of either saline, or leptin, or leptin plus xanthenone (ACE2 activator), or xanthenone (XTN) alone. SBP, serum ACE, ACE2, endothelin-1, E-selectin and ICAM-1 levels were estimated; also their gene expressions were determined in the kidney and aorta respectively. Compared to control, SBP was higher in the leptin-only treated group (P<0.001) and lower in rats treated with xanthenone alone (P<0.01). Proteinuria, markers of endothelial activation were significantly higher than controls in leptin-only treated rats (P<0.05). ACE2 activity and expression were lower in leptin-only treated rats when compared to controls (P<0.05). It seems, leptin administration during pregnancy significantly increases SBP, proteinuria, endothelial activation, but decreases ACE2 level and expression. These effects are prevented by concurrent administration of xanthenone.